Impact of a priority system on patients in waiting lists for knee arthroplasty. Issue 1 (29th September 2014) - Tebé, Cristian; Comas, Merce; Adam, Paula; Solans‐Domènech, Maite; Allepuz, Alejandro; Espallargues, Mireia
Abstract Rationale, aims and objectives The Agency for Health Quality and Assessment of Catalonia (AQuAS) developed a system for the prioritization of patients on non‐urgent waiting lists for cataract as well as knee and hip arthroplasty. The aim was to evaluate the impact of the priority system's application for primary knee arthroplasty (PKA). Methods A retrospective evaluative study with data from the Data Tracking and Management Registry of the CatSalut Waiting Lists for PKA of hospitals in the public hospital network in the period 2003–2009. A description of the characteristics of patients on waiting lists was made and the association between priority scoring and waiting time and the order of operation analysed. Finally, waiting times were simulated that patients would have experienced if being operated on strictly according to a first in first out system or one of priority scoring, to compare them with real waiting times. Results The number of people included on waiting lists for PKA was 67 403. 67% had a priority score. The distribution of the priority score was negatively skewed with an average score of 70 points. The association with the priority score for the waiting time as well as the order of the operations performed was practically null. Conclusions The study concludes that, globally, the prioritization system for PKA has been implemented but had no effect on the prioritization of patients based on their severity. Nevertheless, in some centres, a moderate correlation between the order of operations performed and the priority score was identified.